Early Pregnancy Screening for Women at High-Risk of GDM Results in Reduced Neonatal Morbidity and Similar Maternal Outcomes to Routine Screening - Erin Clarke; Thomas J. Cade; Shaun Brennecke (Journal of Pregnancy)
The Australasian Diabetes in Pregnancy Society recommends screening high-risk women for gestational diabetes mellitus (GDM) before 24 weeks gestation, under the assumption that an earlier diagnosis and opportunity to achieve normoglycemia will minimize adverse outcomes. However, little evidence exists for this recommendation. The study objective was to compare the pregnancy outcomes of high-risk women diagnosed with GDM before 24 weeks gestation and routinely diagnosed women after 24 weeks gestation. A retrospective audit was conducted of all pregnancies diagnosed with GDM using International Association of Diabetes and Pregnancy Study Groups criteria over 12 months at a tertiary Australian hospital. Adverse perinatal outcomes were compared between “Early GDM” diagnosed before 24 weeks (n=133) and “Late GDM” diagnosed from 24 weeks (n=636). Early GDM had a significantly lower newborn composite outcome frequency (hypoglycemia, birth trauma, NICU/SCN admission, stillbirth, neonatal death, respiratory distress, and phototherapy) compared to Late GDM (20.3% vs. 30.0%, p=0.02). Primary cesarean, hypertensive disorders, postpartum hemorrhage, birthweight >90th percentile, macrosomia, and preterm birth frequencies were not significantly different between groups. Therefore, high-risk women diagnosed with GDM in early pregnancy were not more likely to have an adverse outcome compared to routinely diagnosed women. As they are a high-risk group, this may indicate a possible benefit to the early diagnosis of GDM.